2015
DOI: 10.17507/tpls.0502.05
|View full text |Cite
|
Sign up to set email alerts
|

Iranian EFL Students’ Listening Comprehension Problems

Abstract: Abstract-English as a Foreign Language (EFL) listening skill is considered a problematic skill particularly in a foreign language context where practice opportunities are limited. This study aimed to explore the listening comprehension problems of a group of EFL learners. Survey method was followed to collect data from a group of Iranian tertiary level EFL learners (n = 100) using the Listening Comprehension Processing Problems Questionnaire. The results indicated that the learners experienced moderate to high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 29 publications
(27 reference statements)
2
23
0
1
Order By: Relevance
“…3.68 1.08 High *Means values ≤ 2 (low), 2-3.4 (moderate); and ≥ 3.5 (high) levels of listening problems The next-highest levels of problems in the utilization phase were 'Understanding words but not the intended message', 'Difficulty in comprehending the order of ideas in text', and 'Difficulty in deriving the supporting ideas'. In contrast to the participants of Nowrouzi et al (2015), the subjects in the current study reported a moderate level of difficulty in obtaining details.…”
Section: Utilization Problemsmentioning
confidence: 62%
See 1 more Smart Citation
“…3.68 1.08 High *Means values ≤ 2 (low), 2-3.4 (moderate); and ≥ 3.5 (high) levels of listening problems The next-highest levels of problems in the utilization phase were 'Understanding words but not the intended message', 'Difficulty in comprehending the order of ideas in text', and 'Difficulty in deriving the supporting ideas'. In contrast to the participants of Nowrouzi et al (2015), the subjects in the current study reported a moderate level of difficulty in obtaining details.…”
Section: Utilization Problemsmentioning
confidence: 62%
“…The difficulty of recognizing and understanding grammatical structures could be due to a lack of interest. Researchers recommended that vocabulary building, improving syllabi, and providing appropriate English labs can help resolve such problems (Kazouz, 2014;Nowrouzi et al, 2015;Assaf, 2015;Eltayeb, 2017). To summarise, a review of the literature confirms that listening in language acquisition is a worthy topic of research.…”
Section: Previous Studies On Listening Problemsmentioning
confidence: 99%
“…Much attention to the study of students' listening comprehension conducted by some researcher (Zhang et al, 2011;Hamouda 2013;Nowrouzi 2015). Listening is an important skill; it enables language learners to receive and interact with language input and facilitates the emergence of other language skills (Vandergrift 2006 andGoh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, listening plays a crucial role in helping language learners acquire vocabulary and correct pronunciation because there is a strong correlation between vocabulary and listening. Listeners might recognize 50% of the words in a passage and make use of them unintentionally while trying to understand the meaning (Paran, 1996;Milton, Wade & Hopkins, 2010;Nowrouzi, Tam, Zareian, & Nimehchisalem, 2015). Improving vocabulary always involves the receptive skills of listening and reading.…”
Section: Introductionmentioning
confidence: 99%